Identification of a novel inherited ALK variant M1199L in the WNT type of medulloblastoma - Trubicka, Joanna; Szperl, Małgorzata; Grajkowska, Wiesława; Karkucińska-Więckowska, Agnieszka; Tarasińska, Magdalena; Falana, Katarzyna; Dembowska-Bagińska, Bożenna; Łastowska, Maria (Folia Neuropathologica, 2016)
Rearrangements involving the ALK gene were identified in a variety of cancers, including paediatric tumour neuroblastoma where presence of ALK expression is also associated with adverse prognosis. Microarrays data indicate that ALK is expressed in another paediatric tumour – medulloblastoma. Therefore, we investigated if the ALK gene is mutated in medulloblastoma and performed simultaneously the molecular profiling of tumours. Tumours from sixty-four medulloblastoma patients were studied for detection of ALK alterations in exons 23 and 25 using Sanger method. The molecular subtypes of tumours were identified by detection of mutations in the CTNNB1 gene, monosomy 6 and by immunohistochemistry using a panel of representative antibodies. Among three ALK variants detected two resulted in intron variants (rs3738867, rs113866835) and the third one was a novel heterozygous variant c.3595A>T in exon 23 identified in the WNT type of tumour. It resulted in methionine to leucine substitution at codon position 1199 (M1199L) of the kinase domain of ALK protein. Results of analysis using three in silico algorithms confirmed the pathogenicity of this single nucleotide variation. The same gene alteration was detected in both patient and maternal peripheral blood leukocytes indicating an inherited type of the detected variant. Presence of ALK expression in tumour tissue was confirmed by immunohistochemistry. The tumour was diagnosed as classic medulloblastoma, however with visible areas of focal anaplastic features. The patient has been disease free for 6 years since diagnosis. This is the first evidence of an inherited ALK variant in the WNT type of medulloblastoma, what altogether with presence of ALK expression may point towards involvement of the ALK gene in this type of tumours.